EXPERIMENTAL ANALYSIS OF THERMAL PERFORMANCE OF SOLAR AIR COLLECTORS WITH ALUMINUM FOAM OBSTACLES - Bayrak, Fatih; Öztop, Hakan Fehmi (Turkish Soc Thermal Sciences Technology, 2015)
An experimental study has been performed to investigate the energy analysis of flat-plate solar air collectors (SACs) with porous obstacles at two different thicknesses and without obstacles (flat plate). As a porous material aluminum foams are used. They are placed sequentially and in a staggered manner onto the cover of the SACs. The measurements are performed at two different values of air mass flowrate as 0.016 kg/s and 0.025 kg/s and with thickness of 6 mm and 10 mm. Energy efficiencies of SACs are calculated based on first law of thermodynamics. In the experiments, five types of solar air collectors are tested and a comparison is made among them from the point of energy efficiency. The obtained results showed that the highest collector efficiency and air temperature rise are achieved by SACs at 6 mm thickness and 0.025 kg/s air mass flowrate.
Keywords: Solar air heaters; thermal efficiency; energy; heat transfer; porous obstacles